Decompensated Cirrhosis after Renal Transplantation: A Case Report - Vinay Patel; Luis Marsano; Mary Eng (Case Reports in Transplantation)
Patients with end-stage liver disease with renal failure can be considered for simultaneous liver kidney transplantation. There are, however, no clear guidelines as to the management of the well-compensated cirrhotic patient with end-stage renal disease. We present the case of a patient with cirrhosis who decompensated after renal transplantation. With no indication for liver transplantation, can these patients safely undergo renal transplantation?